2014
DOI: 10.1103/physrevd.89.014014
|View full text |Cite
|
Sign up to set email alerts
|

Self-similarity and the Froissart bound

Abstract: The Froissart bound implies that the total cross section (or, equivalently, the structure function) cannot rise faster than the logarithmic growth of $ \ln^{2} \left(\frac{1}{x} \right)$. In this work, we show that such a slow growth is not compatible with the notion of self-similarity. As a result, it calls for the modification of the defining transverse-momentum-dependent parton density function (TMD PDF) of a self-similarity based proton structure function $F_{2} \left(x,Q^{2} \right)$ at small \textit{x}. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…It needs at least three magnification factors not two as compared to earlier work in Ref. [45]. The ranges of validity for four different self-similarity based models with three magnification factors are: Thus the above analysis shows the Froissart saturated self-similarity based structure function has smaller validity ranges as compared to that of structure function without Froissart condition having power law growth in 1 x and log Q 2 .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…It needs at least three magnification factors not two as compared to earlier work in Ref. [45]. The ranges of validity for four different self-similarity based models with three magnification factors are: Thus the above analysis shows the Froissart saturated self-similarity based structure function has smaller validity ranges as compared to that of structure function without Froissart condition having power law growth in 1 x and log Q 2 .…”
Section: Discussionmentioning
confidence: 80%
“…. It was noted in [45] that if the magnification factor M 2 is changed to log 1 x , then it is possible to get a Froissart saturation like behavior in structure function. However, we observe that it is true only for PDF but not for the structure function.…”
Section: A Froissart Bound In Self-similarity Based Proton Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Ref [39]. In a recent study [40], it is suggested that the logarithmic rise in Q 2 of structure function is also possible, in an improved singularity free self-similar based model with a wider kinematical range in x and Q 2 but even then it is far short off accounting the entire x − Q 2 range explored in HERA unlike perturbative QCD [28].…”
Section: Discussionmentioning
confidence: 99%
“…Self-similarity is a possible feature of multi-partons inside a proton at small x suggested by Lastovicka [1] and pursued by us in recent years [2,3,4,5,6]. More recently, we have examined its consequences in [7] double parton distribution function(dPDF) to be tested at LHC, in Froissart saturation [8] and Longitudinal structure function [9].…”
Section: Introductionmentioning
confidence: 99%